Two case reports of less invasive surgery using interceed (oxidized regenerated cellulose) absorbable adhesion barrier for vaginoplasty in Meyer-Rokitansky-Küsterhauser syndrome - Inagaki, Mieko; Motoyama, Satoru; Laoag-Fernandez, Jovelle B; Yasuda, Ritsuko; Maruo, Takeshi (International surgery, 2009)
The objective of this case study is to present our experiences of a surgical innovative approach for vaginal agenesis using Interceed. The present report involved two subjects diagnosed to have vaginal agenesis due to Mayer-Rokitansky-Kiister-Hauser syndrome. Operation procedure involved the creation of a neovaginal tunnel and then a mold wrapped with Interceed was placed in the neovagina. The duration of surgery was around 30 min with minimal blood loss. Hospitalization stay was only 2 days after the procedure, with no operative and postoperative complications. Epithelialization of the neovagina was achieved within a month after surgery. The patients were satisfied with the outcome. The neovagina created with this procedure was the same with the normal adult vagina histologically and physiologically. In conclusion, the creation of a neovagina using Interceed resulted in favorable outcome and this approach may be a potential alternative to the management of vaginal agenesis.